Discussions about the work in the literature class from the poem Morte e Vida Severina (Research, Society and Development, 2021)
This research deals with the study of the poem Morte e Vida Severina from the perspective of work and aims to present a didactic sequence working on the theme discussed here as a way to contribute to the work of the Literature teacher in Professional and Technological Education. As a methodology, bibliographic research was used, bringing together authors such as Saviani (1994) and Sobral (et al, 2016), who discuss work as an educational principle, and Dolz, Noverraz and Schneuwly (2004), who address the methodology of the didactic sequence . As a result, a didactic sequence was obtained with three steps developed in four classes which follow a proposal for presentation, development and final production which can contribute to a reflective teaching of literature, addressing not only the poem itself, but also the challenges faced in the world of work from the problems experienced by the character Severino. It is concluded that planning for an interdisciplinary class requires time and dedication, however, it is a necessary effort when it comes to seeking to include in the pedagogical practice a teaching based on the principles of professional and technological education.